Novel low-temperature synthesis of nanosized NiZn ferrite - Verma, S.; Pradhan, S. D.; Pasricha, R.; Sainkar, S. R.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2005)
Nanosized NiZn ferrite powder is synthesized by a low-temperature method, using a unique combination of citric acid and glycine. An appropriate molar ratio of both citric acid and glycine offers a low-temperature synthetic route by incorporating the complexation behavior of citric acid and the combustion nature of glycine. Thermal decomposition/controlled autocatalytic combustion of the composite gel occurs at a low temperature of around 175 degrees C, with the evolution of a large amount of gases. Transmission electron microscopic studies showed that the average particle size of the ferrite obtained is similar to 2.5 nm, with a narrow size distribution. Uniformly distributed fine-grained microstructure with low porosity is obtained for a sample sintered at 1000 degrees C.

Novel polymer-inorganic solid-state reaction for the synthesis of CdS nanocrystallites - Kanade, K. G.; Hawaldar, Ranjit R.; Pasricha, R.; Radhakrishnan, S.; Seth, T.; Mulik, Uttam P.; Kale, B. B.; Amalnerkar, Dinesh P. (Materials Letters, 2005)
We offer a novel polymer-inorganic solid-state reaction route for the in situ generation of nanochalcogenide semiconductor in the network of polymer which itself acts as a chalcogen source. We have exemplified feasibility of this route by reacting CdI2 with engineering thermoplastic polyphenylene sulphide (PPS). These two reactants in 1:1 and 10:1 molar ratios were simply heated at the crystalline melting temperature of PPS. The resultant products were characterized by X-ray diffractometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM, with selected area electron diffraction). The prima facie observations revealed the formation of cubic nanocrystallites of US with the particle size ranging from 6 to 20 nm entrapped in modified (cyclized) PPS matrix when the reactants were taken in 10:1 molar ratio. A tentative mechanism has been suggested for such hitherto unattempted solid-state reaction. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdS nanocrystallites; Semiconductor; solid-state reaction; Thermoplastic polymer matrix